Effect of fatigue on knee kinematics and kinetics during sidestep cutting and single leg landing in female handball athletes - Souza Bedo, B. L.; Catelli, D.; Lamontagne, M.; Moraes, R.; Rodrigues Pereira, D.; Pereira Santiago, P. R. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to investigate the effect of fatigue in knee biomechanics in female handball athletes during the sidestep cutting and single-leg landing. Twenty female handball athletes participated in this study. The fatigue protocol was composed of specific handball movements/actions. The participants performed three trials of the sidestep cutting and single-leg drop landing before (baseline) and after the fatigue protocol. The effect of the fatigue was compared using a paired t-test compared using statistical parametric mapping. During sidestep cutting, the athletes performed the task with lower knee flexion and greater knee abduction during the fatigue state. During the single-leg landing, an increase in the knee valgus was found during the fatigue state. No difference was found on knee kinetics. The fatigue impacted the knee kinematics decreasing the knee flexion during the sidestep cutting and increasing the knee valgus during both, sidestep cutting and single-leg landing tasks.